The Analysis of Government Intervention and Stock Market during Crises Periods - Fiesty Utami; Ai Chi Hsu (Jurnal Internasional Penelitian Bisnis Terapan, 2019)
The government, through central banks, has a monetary authority to do an intervention, either directly or indirectly. Central banks do a direct intervention by exchanging reserves to influence the exchange rate and do an indirect intervention by increasing or decreasing the interest rate. However, when the currency crises happen, smoothing the currency movements by doing government intervention may reduce fears in the financial markets. This study examines the government intervention effect in 27 countries on the stock market during the crises periods, either during the Asian currency crises or currency crises of each country. To estimate abnormal returns, this study uses the traditional market model. Then, in the lack of official government intervention data, this study uses the proxy of government intervention to estimate the intervention activities. This study shows that in currency crises periods, the government interventions do not effectively impact exchange rate, stock price, and stock market return.